Generation and Characterization of Atmospheric Pressure Air Plasma and Finding its Applications (Global Journal of Science Frontier Research, 2013)
A high voltage RF plasma source is designed to produce atmospheric pressure air plasma. The plasma is produced at different electrode configurations. Properties of such plasma depend on several parameters such as frequency of the plasma generating source, input power and gas flow rate. The produced plasma is characterized by different diagnostic techniques in order to determine gas temperature, electron temperature, and electron density. It is desired to find out applications of such atmospheric pressure air plasma in food processing, surface modification, and material processing. One of the most fascinating applications of atmospheric pressure plasmas is its use for biomedical applications because of its capability of producing various biocidal agents including reactive species, UV radiation, and charged particles [1].
Keywords: plasma; atmosphere; biomedical; species